Pengaruh Model Teams Games Tournament (TGT) terhadap Motivasi Belajar Matematika Berdasarkan Gender Siswa Sekolah Dasar - Ginting, Fauziah Azzuardini (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
The background of this research is that students are less motivated in learning and do not understand mathematical concepts. The problem in this research is limited to the lack of student motivation in the mathematics learning process and the Teams Games Tournament (TGT) type cooperative learning model is rarely applied in the mathematics learning process. The aim of this research is to determine the effect of the Teams Games Tournament (TGT) model on elementary school students' motivation to learn mathematics based on gender. The research method used in this research is quantitative methods. This type of research uses a quasi-experimental method (Quasy Experiment). The research was carried out at SDN 091482 Kasindir, Jorlang Hataran District, Simalungun Regency from September 4 to September 9 2023 in the odd semester of the 2023/2024 academic year. Based on the results of descriptive analysis data obtained from the students' learning motivation progress scores that were tested, in the male initial questionnaire, the average questionnaire score was 38.67, the standard deviation was 1,231, the maximum score was 41, and the minimum score was 36. Initial questionnaire women obtained an average score from the questionnaire results of 39.92, a standard deviation of 1,256, a max score of 43, and a minimum score of 38. Meanwhile, in the final questionnaire for men, the average score of the questionnaire results was 39.83, the standard deviation was 1,337, the The maximum value is 42, and the minimum value is 38. And in the final questionnaire for women, the average value of the questionnaire results was 40.54, the standard deviation was 1,330, the maximum value was 42, and the minimum value was 38. Based on the results of this research, the author put forward suggestions namely, 1). Students are expected to always be active and pay attention to the teacher's explanations during the learning process. 2). For all teachers, they must always innovate and be able to adapt to be able to use various learning methods so that students do not get bored easily in the learning process.